CODEA : an agent based multi-objective optimization framework - Castro-Gutierrez, Juan; Landa-Silva, Dario; Moreno-Perez, Jose (2010)
This work presents CODEA, a COoperative DEcentralized Architecture for Multiobjective Optimization. CODEA is an objectoriented framework that aims at the creation of groups of agents to tackle complex problems by cooperative search. This cooperation is carried out without any individual controlling the cooperation nor the behaviour of the agents. Each agent works on its own to improve itself and collaborates to improve the performance of the group by sharing information.